The implications of global and domestic credit cycles for emerging market economies: Measures of finance-adjusted output gaps - Ioannis Grintzalis; David Lodge; Ana-Simona Manu (European Central Bank (ECB), 2017)
We present estimates of finance-adjusted output gaps which incorporate the information on the domestic and global credit cycles for a sample of emerging market economies (EMEs). Following recent BIS research, we use a state-space representation of an HP filter augmented with a measure of the credit gap to estimate finance-adjusted output gaps. We measure the domestic and global credit gaps as the deviation of private-sector real credit growth and net capital flows to EMEs from long-term trends, using the asymmetric Band-Pass filter. Overall, we find that financial cycle information is associated with cyclical movements in output. In the current circumstances, the estimates suggest that if financing and credit conditions were to tighten, it would be associated with a moderation in activity in some EMEs.
Keywords: C32; E32; F32; 330; domestic credit cycle; global financial cycle; output gap